Investigation of an Intense Dust Outbreak in the Mediterranean Using XMed-Dry Network, Multiplatform Observations, and Numerical Modeling - Umberto Rizza; Konrad Kandler; Melanie Eknayan; Giorgio Passerini; Enrico Mancinelli; Simone Virgili; Mauro Morichetti; Michael Nolle; Konstantinos Eleftheriadis; Vasiliki Vasilatou; Pierina Ielpo (Applied Sciences, 2021)
The Weather Research and Forecasting (WRF) model with online coupled chemistry (WRF-Chem) is applied to study an intense Saharan dust outbreak event affecting the Italian peninsula in 15 and 16 April 2018. According to the MODIS retrievals, this intrusion was characterized by an intense aerosol optical depth (AOD) peak value in the southern Mediterranean. Measurements within the Dry Deposition Network Across the Mediterranean (XMed-Dry) are compared with the output of the WRF-Chem model. XMed-Dry samples from Lecce (Italy), Athens (Greece) and San Lawrenz/Gozo (Malta) were analysed with respect to aerosol particle size distribution, relative dust contribution, and composition. The discrepancy between the model and measured deposition indicate the need to formulate in WRF-Chem more sophisticated deposition schemes, this will need to evaluate the sensitivity of the results to the precise particle size limits chosen for the aerosol model. Moreover, satellite retrievals from MODIS sensors elaborated with the MAIAC algorithm, Aeronet stations, and measurements of <semantics>PM10</semantics> at the selected sites were also considered. In a numerical domain that spans the Mediterranean and the northern Saharan desert, two different dust emission schemes, namely Gocart-AFWA and the Shao-2001, were tested and compared with multiplatform observations for simulation period covering the dust outbreak. Actual results indicate that both emission schemes would benefit from replacing the static erodibility map and soil particle distribution with remote sensed and in-situ observational data.